The Role of Management by Exception in Achieving Entrepreneurial Leadership - Medany, Elderdery Ahmed Ismail (Journal of Economic, Administrative and Legal Sciences, 2017)
The aim of this study is to highlight the role that management by exception plays in achieving pioneering leadership and the survival and growth of institutions and trying to increase their effectiveness and performance in light of the great challenges they face. The importance of management is characterized by adding value to the institution, creating a competitive advantage, making the institution more flexible, and adopting the forms of coordination, designing and structuring. The problem of the study is represented in this question: is the application of the concept of management by exception leads to entrepreneurial leadership in business organizations? The study showed that the entrepreneurial leadership has the ability to influence workers and the performance of institutions. Based on the principles and the basis of modern leadership and management, it is possible for organizations to achieve proactive entrepreneurship among other organizations. by applying entrepreneurial leadership and sorting out the appropriate decisions